Surface Functionalization of an Aluminum Alloy to Generate an Antibiofilm Coating Based on Poly(Methyl Methacrylate) and Silver Nanoparticles - Rabagliati-Canessa, F; Encina-Rojas, M; Paez-Collio, M; Paez-Collio, M; Zagal-Moya, J; Zagal-Moya, J; Gulppi-Cabra, M; Gulppi-Cabra, M; Azocar-Guzman, M; Azocar-Guzman, M; Muñoz-Moena, L; Muñoz-Moena, L (Multidisciplinary Digital Publishing Institute (MDPI), 2018)
An experimental protocol was studied to improve the adhesion of a polymeric poly(methyl methacrylate) coating that was modified with silver nanoparticles to an aluminum alloy, AA2024. The nanoparticles were incorporated into the polymeric matrix to add the property of inhibiting biofilm formation to the anticorrosive characteristics of the film, thus also making the coating antibiocorrosive. The protocol consists of functionalizing the surface through a pseudotransesterification treatment using a methyl methacrylate monomer that bonds covalently to the surface and leaves a terminal double bond that promotes and directs the polymerization reaction that takes place in the process that follows immediately after. This results in more compact and thicker poly(methyl methacrylate) (PMMA) coatings than those obtained without pseudotransesterification. The poly(methyl methacrylate) matrix modified with nanoparticles was obtained by incorporating both the nanoparticles and the methyl methacrylate in the reactor. The in situ polymerization involved combining the pretreated AA2024 specimens combined with the methyl methacrylate monomer and AgNps. The antibiofilm capacity of the coating was evaluated against P. aeruginosa, with an excellent response. Not only did the presence of bacteria decrease, but the formation of the exopolymer subunits was 99.99% lower than on the uncoated aluminum alloy or the alloy coated with unmodified poly(methyl methacrylate). As well and significantly, the potentiodynamic polarization measurements indicate that the PMMA-Ag coating has a good anticorrosive property in a 0.1-M NaCl medium. © 2018 by the authors.
Keywords: coating; antibiofilm; functionalization; poly(methyl methacrylate); aluminum alloy